An experimental and computational study of pyrimidine based bis-uracil derivatives as efficient candidates for optical, nonlinear optical, and drug discovery applications. Issue 14 (17th July 2020) - Mohan, Bharti; Choudhary, Mukesh; Kumar, Gaurav; Muhammad, Shabbir; Das, Neeladri; Singh, Khushwant; Al-Sehemi, Abdullah G.; Kumar, Santosh
Abstract: Three novel pyrimidine based bis-uracil derivatives 1–3 were synthesized by the condensation reaction of 2-hydroxynaphthaldehyde with 6-amino-1, 3-dimethylpyrimidine-2, -4(1H, 3H)-dione; 6-amino-1, 3-diethylpyrimidine-2, -4(1H, 3H)-dione, and 6-amino-1, -ethyl-3-methylpyrimidine-2, -4(1H, 3H)-dione, respectively and structurally characterized. The preliminary test of compounds was evaluated by SwissADME that can predict rapidly key parameters for a collection of molecules to support their drug discovery endeavors. Antimicrobial, photoluminescence, and molecular docking of compounds were also studied. The kinetic and thermal stabilities along with intramolecular charge transfer characters were obtained for compounds using frontier molecular orbitals, electrostatic potential diagrams as well as their orbital energies. Additionally, we applied state-of-art computational methods to assess the linear and nonlinear optical (NLO) properties of compounds at M06/6-311G** levels of theory. The third-order NLO properties of 1–3 were observed larger as compared to the standard indicating the considerable NLO character of all molecules, which may render the above derivatives as efficient candidates for NLO device fabrications. Graphical Abstract: